TELAAH SOFTWARE HADIS “SATU HARI SATU HADIS” KARYA PUSAT KAJIAN HADIS DALAM RANGKA PEMENUHAN KEBUTUHAN INFORMASI MAHASISWA DI UIN IMAM BONJOL PADANG - Nasrul Makdis (Info Bibliotheca: Jurnal Perpustakaan dan Ilmu Informasi, 2021)
Hadith in the Android era that has developed in the form of hadith software. One of the hadith software by the Hadith Study Center that is loved by Ahmad Lutfi Fathullah is "One Day One Hadith". "One Day One Hadith" is a hadith software that is useful to help direct the process of memorizing hadith every day with the traditions of the Prophet SAW. thematic and simple selection of the history of Sahih Bukhari. Analytical descriptive method through a review of the "One Day One Hadith" application, starting from describing the "One Day One Hadith" software, the presentation pattern of the hadith, its advantages and disadvantages. The results of this study will describe the "One Day One Hadith" software, the pattern of presenting the hadith, its advantages and disadvantages